Development of Tourist Attraction In Asahan Regency (Case of Kelapa Gading Lake) - Sitti Nurlaeli; M. Halfi Indra Syahputra (Nawasena: Jurnal Ilmiah Pariwisata, 2022)
Tourism development is carried out aiming to make tourism go forward and develop towards a better quality in terms of infrastructure and facilities, facilitate access to tourist attractions. This study aims to provide a design overview of the development of Lake Kelapa Gading Tourism Object. The method used is qualitative descriptive. The conditions of development aspects of tourism areas analyzed include: tourist attraction, accessibility, infrastructure and facilities, social support of the community. All aspects are translated into indicators that form the basis of the compilation of tourist object checklists. The results show that aspects of infrastructure and facilities are still not optimal compared to other aspects. Aspects that need to be prioritized in the development of Lake Kelapa Gading Tourism Object are aspects of infrastructure and facilities. Related to this aspect, it is necessary to improve and complete the facilities and facilities of tourism objects.